Vida de mulheres negras, professoras universitárias da Universidade Federal de Santa Maria - Quadros, Taiana Flores de (2015)
This study aims to dialogue with black teachers at the Federal University of Santa Maria (UFSM), trying to understand which pathways and mishaps were experienced by such teachers, until they came to teaching in higher education, and realize the extent to which social relations ethno racial and gender interfere with their teaching practices. The topic to be presented and dialogue in this study is related more broadly to research in education, taking as a guideline the education of ethnic-racial relations and educational proceedings brought by black women, teachers in higher education, especially in processes where experienced or not racism and discrimination in the education sector. In this sense, this present study assumes that Brazilian universities, today, are in a situation of inequality, where black students constitute themselves as a minority and when observing the teaching staff (as), the situation is even more alarming. Many studies have proven that data, which show racism - social, cultural and economic - that prevails in our society, such as Henriques (2002); Pine (2008); Queiroz (2001, 2002); Rosemberg (2008, 2009) Munanga (1999, 2006). With regard to gender issues, one has to refer the Scott studies (1995), Safiotti (2004), Blonde (1997, 2008). The results of this study, drawn from data collected from PROGEP and analysis of the life story of black self-declared Professor of UFSM, demonstrate the existing racial confinement in UFSM. The teacher narratives lead to evidence that social mobility and the experiences throughout life mean that many times, some people perceive blacks as "other", showing a gap between with this group. Thus, the gap created by their life experiences, makes understand prejudice and discrimination against the black as a class condition and not a condition of phenotype / brands, but recognizes the difference between black and white. In this sense, the study shows that the positioning presented by the teacher regarding racial ethnic issues, causes she to be positioned in the same way in the teaching practice.